Divergence of Genes Encoding CITED1 and CITED2 in Blunt Snout Bream (Megalobrama amblycephala) and Their Transcriptional Responses to Hypoxia - Sun, Yuan; Guo, Hong-Hong; Guo, Dan-Dan; Jiang, Xia-Yun; Zou, Shu-Ming (Frontiers in Physiology, 2018)
The proteins CITED belong to a family of non-DNA-binding transcriptional co-regulators involved in the regulation of various transcriptional responses. Previous studies suggest that members of CITED family may function in response to hypoxia in mammals. however, the molecular and functional information on CITED genes in aquaculture fish is unclear. Here, we characterized and examined the transcriptional patterns of CITED1 and CITED2 genes in the hypoxia-sensitive blunt snout bream (Megalobrama amblycephala). Blunt snout bream CITED1 and CITED2 genes shared a relatively low sequence identity of 45%. CITED1 and CITED2 mRNAs were widely transcribed in adult tissues. During embryogenesis, CITED1 mRNA was significantly transcribed at 4, 24, 28, 40, and 44 hpf, whereas CITED2 mRNA levels fluctuated from the zygote to 44 hpf larval stage. Whole-mount in situ hybridization demonstrated that CITED1 and CITED2 mRNAs were detected in the brain at 12 hpf, brain and gut at 24 hpf, and brain at 36 hpf. In addition, low expression of CITED1 mRNA was detected in the tailbud at 24 hpf. The results of acute hypoxia experiment showed that CITED1 and CITED2 mRNAs were markedly upregulated in the kidney and downregulated in the liver, brain, gill, and heart under hypoxia. Embryos in hypoxic conditions at different developmental stages showed a significant increase in mRNA levels of CITED1 and CITED2. These results provide a new insight into the divergence of CITED1 and CITED2 genes and their transcriptional responses to hypoxia.